Macroeconomic determinants of Ecuadorian migratory flows to the United States, period 1990 – 2020 - Vizuete Guadalupe, Jervis (2023)
Migration theories are used to explain this phenomenon. In the case of Ecuador, the theory of Neoclassical Macroeconomics is applied and the literature suggests comparing macroeconomic indicators between the country of origin and the recipient of migrants. The background indicates several factors that influence the decision to migrate. In this study, the Human Development Index, GDP per cápita, unemployment rate, public spending as a percentage of GDP and the inflation rate are used as determinants to describe the migration phenomenon. A pearson evaluation matrix is made to evaluate the relationship between the dependent and independent variable. Through a step-by-step multiple linear regression model, non-significant variables are excluded, in this case, the Human Development Index. The remaining variables will be maintained considering their level of significance. These variables explain 84,10% of the migratory flow from Ecuador to the United States during the period 1990-2020. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/2241